A Comparison of Criminal Record Regulations in France and Indonesia as a Process of Social Reintegration for Defendants Granted Judicial Pardon - Fortuna Sutrisno, Bethree Crystala; Djatmika, Prija (International Journal of Business, Law, and Education, 2026)
This study examines the expungement of criminal records as a consequence of a judicial pardon, comparing the regulations governing this process in France and Indonesia. The methodology employed is a normative legal analysis using a comparative law approach. The research findings indicate that France has more systematic mechanisms in place to restrict access to and the retention period for criminal records, including rehabilitation and automatic expungement under certain conditions. Meanwhile, Indonesia lacks comprehensive regulations governing the expungement of criminal records following a judge’s pardon, which could result in ongoing stigma for individuals. Therefore, a reformulation of legal policy in Indonesia is necessary to ensure a balance among legal certainty, public protection, and the right to rehabilitation for offenders who have been granted judicial pardon.